Development of an mRNA replacement therapy for phenylketonuria - Carlos G. Perez-Garcia; Ramon Diaz-Trelles; Jerel Boyd Vega; Yanjie Bao; Marciano Sablad; Patty Limphong; Simon Chikamatsu; Hailong Yu; Wendy Taylor; Priya P. Karmali; Kiyoshi Tachikawa; Padmanabh Chivukula (Elsevier, 2022)
Phenylketonuria (PKU) is an inborn error caused by deficiencies in phenylalanine (Phe) metabolism. Mutations in the phenylalanine hydroxylase (PAH) gene are the main cause of the disease whose signature hallmarks of toxically elevated levels of Phe accumulation in plasma and organs such as the brain, result in irreversible intellectual disability. Here, we present a unique approach to treating PKU deficiency by using an mRNA replacement therapy. A full-length mRNA encoding human PAH (hPAH) is encapsulated in our proprietary lipid nanoparticle LUNAR and delivered to a Pahenu2 mouse model that carries a missense mutation in the mouse PAH gene. Animals carrying this missense mutation develop hyperphenylalanemia and hypotyrosinemia in plasma, two clinical features commonly observed in the clinical presentation of PKU. We show that intravenous infusion of LUNAR-hPAH mRNA can generate high levels of hPAH protein in hepatocytes and restore the Phe metabolism in the Pahenu2 mouse model. Together, these data establish a proof of principle of a novel mRNA replacement therapy to treat PKU.